Leveraging EUnetHTA's conceptual framework to compare HTA decision drivers in France, Italy, and Germany from a manufacturer's point of view - Giovanni Giuliani; Frederic Chassagnol; David Traub; Marlene Gyldmark; Ansgar Hebborn; Pierre Ducournau; Jörg Ruoff (Health Economics Review, 2018)
Background: Health Technology Assessments (HTA) procedures differ substantially across the various European countries. We reviewed recent appraisals of a pharmaceutical manufacturer in three major European markets (France; Italy; Germany) and identified and categorized related decision drivers. Methods: New marketing authorisation between January 2011 and August 2017, and Roche being the Marketing Authorization Holder, were included. Outcome of HTA appraisals by the Haute Autorité de Santé (HAS), Agenzia Italiana del Farmaco (AIFA), and Federal Joint Committee (Gemeinsamer Bundesausschuss, G-BA) were reviewed. Respective decision drivers were identified and commonalities and differences across the three countries were determined leveraging the EUnetHTA conceptual taxonomy (i.e. the 9 domains of the EUnetHTA core model). Results: Within that time period Roche received European marketing authorization for eight new molecular entities (10 indications, respectively). Outcome of HTA appraisals was heterogeneous across the three countries. However, the four clinical domains of the EUnetHTA core model were driving the national HTA appraisals, with the clinical effectiveness domain being of most importance. Important drivers related to the other three clinical domains included the target patient population (subgroups, Germany), the current management of the condition (unmet need, Italy), the regulatory status (Orphan Designation, Germany), as well as safety considerations (all three countries). Average time between EMA approval and full commercial availability of new medicines was 63 (Germany), 459 (Italy), and 557 days (France). Conclusions: The clinical domains of the EUnetHTA framework are mainly driven by national HTA appraisals, providing a suitable starting point for further developing a joint European view on value and evidence. Underlying topics and issues still reveal considerable differences.
Keywords: 330; Appraisal; EUnetHTA Core model; Health technology assessment; Innovation; HAS; AIFA; G-BA